2021
DOI: 10.1093/clinchem/hvab068
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interlaboratory Reproducibility of the Sensitivity to Endocrine Therapy Assay for Stage II/III Breast Cancer

Abstract: Background The sensitivity to endocrine therapy assay (SET2,3) predicts treatment outcomes in Stage II-III breast cancer. SET2,3 measures transcription related to estrogen and progesterone receptors (SETER/PR index) and the molecular subtype (RNA4: ESR1, PGR, ERBB2, AURKA) from formalin-fixed paraffin-embedded (FFPE) tissue sections. Methods We designed a nested study across 3 pathology laboratories, each testing 60 breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Another limitation is that SET2,3 results were inferred from Agilent microarray gene expression measurements rather than the platform used to develop or to perform this test (7,26). It is likely that this introduces some technical inaccuracy, although we had calibrated SET2,3 between genomic platforms to measure SET2,3 from a similar microarray platform to evaluate the I-SPY2 trial (7).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that SET2,3 results were inferred from Agilent microarray gene expression measurements rather than the platform used to develop or to perform this test (7,26). It is likely that this introduces some technical inaccuracy, although we had calibrated SET2,3 between genomic platforms to measure SET2,3 from a similar microarray platform to evaluate the I-SPY2 trial (7).…”
Section: Discussionmentioning
confidence: 99%
“…1 The sensitivity to endocrine therapy (SET2,3) index is a customized assay for formalin-fixed paraffin-embedded tumor tissues, which yields reproducible results within and between different laboratories, offering prognostic information for patients receiving endocrine therapy. [6][7][8] It combines the SET index of transcription related to estrogen and progesterone receptors (SET ER/PR ) with a baseline prognostic index (BPI) derived from pathologic tumor size, nodal involvement, and molecular subtype by RNA4 (ESR1, PGR, ERBB2, and AURKA). [7][8][9] Each component, SET ER/PR index and BPI, added independent prognostic information in prior studies 8,10 and multivariable Cox models of SET2,3 demonstrated that the RNA4 within the BPI could be substituted by contemporary prognostic signatures, but the SET ER/PR index could not be substituted.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] It combines the SET index of transcription related to estrogen and progesterone receptors (SET ER/PR ) with a baseline prognostic index (BPI) derived from pathologic tumor size, nodal involvement, and molecular subtype by RNA4 (ESR1, PGR, ERBB2, and AURKA). [7][8][9] Each component, SET ER/PR index and BPI, added independent prognostic information in prior studies 8,10 and multivariable Cox models of SET2,3 demonstrated that the RNA4 within the BPI could be substituted by contemporary prognostic signatures, but the SET ER/PR index could not be substituted. 8 High SET2,3 scores are associated with endocrine sensitivity and more favorable prognosis, and low SET2,3 scores with endocrine therapy resistance and less-favorable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that the model provided valuable prognostic information for the first 5 years, but not beyond, although this may be in part explained by the fact that endocrine therapy was discontinued after 5 years. In addition, although the authors previously demonstrated reproducibility of this assay with high interlaboratory and interlaboratory concordance, 23 the practical aspect and associated costs are important factors as we navigate the increasing costs of cancer care and cost-effectiveness of gene expression profiling. 24 It is likely that without additional predictive merit, the prognostic aspect would not justify the means or the cost to be routinely used in practice at present.…”
mentioning
confidence: 99%